Avaliação por RM das ATMs em crianças e adolescentes com má-oclusão de classe III e/ou subdivisão de Angle - Tagawa, Daniella Torres [UNIFESP] (2019)
Objective: Evaluate the position and shape ofthe condyle and articular discof the temporomandibular joint (TMJ)in children and adolescents with Angle’s Class III malocclusion with or without subdivision using magnetic resonance imaging (MRI). Methods: The sample consisted of 78 white and brown Brazilian boys (n=31) and girls (n=47) with a mean age of 9.5 years, at a total of 156 TMJs.MRI scans were obtained at treatment baseline. Two observers conducted a qualitative evaluation with the patient’s mouth closed (CM) at habitual occlusion and open (OM).Nonparametric tests were used to assess intra- and interobserver agreement. Results: When condyles were in the CM position, 128 TMJs (82.1%) were concentric.When in OM, the condyles of 44 TMJs (28.2%) showed normal mobility, of 59 (37.8%), hypomobility, and of 53 (34.0%), hypermobility. When the articular disc was in the CM position, discs of 125 TMJs (80.1%) were well positioned, whereas those of 31 TMJs (19.9%) were dislocated. The disc remained interposed in 125 TMJs (80.1%) when in OM position, but was displaced in 31 TMJs (19.9%) after reduction.In 139 TMJs (89.1%), condylar shape was normal, whereas in 17 (10.9%), the condyle was remodeled. The disc was biconcave in 147 TMJs (94.2%) when in CM position and, when in OM position, in 156 TMJs (100%). Conclusion: Important signs of temporomandibular disorders were found, particularly articular disc dislocation. Long-term follow-up and future studies are suggested.